Identification of the Features of Emotional Dysfunction in Female Individuals With Methamphetamine Use Disorder Measured by Musical Stimuli Modulated Startle Reflex - Chen, Xi-Jing; Wang, Chun-Guang; Liu, Wang; Gorowska, Monika; Wang, Dong-Mei; Li, Yong-Hui (Frontiers in Human Neuroscience, 2018)
Emotional dysregulation contributes to the development of substance use disorders (SUDs) and is highly associated with drug abuse and relapse. Music as a contextual auditory stimulus can effectively stimulate the reward circuitry, modulate memory associated with drug taking, and enhance emotional experiences during drug taking. However, the studies of the emotional responses to music in individuals with SUDs are scarce. Using startle reflex and self-reports, this study assessed the psychophysiological and cognitive emotional responses (i.e., valence, arousal, and proximity) to happy, peaceful, and fearful music stimuli in 30 females with methamphetamine use disorder (MUD) and 30 healthy females. The results found that participants with MUD showed an inhibited startle response to fearful music compared to normal controls (t = 3.7, p <.01), and no significant differences were found in the startle responses to happy and peaceful music between the two groups. For the self-reported ratings, participants with MUD showed a decreased arousal in the response to fearful (t = 4.1, p < .01) and happy music (t = 3.8, p <. 01), an increased valence in the response to fearful music (t = 4.4, p <. 01), and a higher level of proximity in the response to fearful (t = 3.8, p < .01) and happy music (t = 2.2, p =.03). No significant differences were found in the rating of arousal to peaceful music, the valence to happy and peaceful music, as well as the proximity to peaceful music between the two groups. The females with MUD showed attenuated psychophysiological response and potentiated cognitive response (i.e., valence, arousal) to fearful music, as well as a high proximity to musical stimuli with high arousal regardless of its valence. These results have important implications for promoting the effectiveness of assessment and therapy selections for female MUD patients with impaired emotion regulation.